Epidemics in history: lessons and limits (Actualizaciones en Sida e Infectología, 2022)
For centuries, history was believed to be a "teacher of life" and it was customary to try to draw lessons from past events. Today, professional historians are reluctant to turn to the past in search of lessons for the present. However, thinking historically allows us to better analyze our present. That is the purpose of this article, to look at the pandemics of the past to give historical perspective to the one we are living in the present.The most shocking epidemic in human history is probably the bubonic plague epidemic that affected Europe between the 14th and 18th centuries. This epidemic had a devastating wave in the 14th century, the "Black Death", which left approximately 200 million dead. It was a contagious disease such as had never been seen before, and to such an extent that the very concept of contagion spread from there in the medical vocabulary. What lessons did this epidemic teach us?As analyzed by medical historian Frank Snowden, at that time mankind learned two things that would be taken up in subsequent epidemics (1). The first lesson was that in times of epidemics, the authorities must turn to physicians to decide what to do. It is possible to argue that the first forms of public health were thus developed. The emergency situation led several cities to summon physicians who formed health boards to implement the policies demanded by the extraordinary situation. From that moment on, recourse to physicians became a common repertoire in all epidemics.The second lesson was the practice of "quarantine" as the only way to stop contagion when there is no known treatment for the disease. In the case of bubonic plague, there was a total lack of knowledge about what transmitted the disease. Faced with this, from the end of the 14th century, the authorities of some cities began to order reclusion. Isolation did not work as a remedy but as a way to prevent the spread of the disease. Thus, the cities were besieged and protected by troops.People were locked in their homes and many neighborhoods isolated from the rest of the city. Of course, these measures were strongly opposed and generated social unrest. Already at that time, the dilemma between economy and health was appearing.During the different waves of bubonic plague, quarantine proved to be the most effective measure to prevent its spread. For Frank Snowden, the greatest endemic disease in European history was not eliminated by the advance of medicine or science but by the deployment of military power and measures taken by the highest political authorities to ensure isolation.But what lessons have we learned from the epidemics that took place in Argentina? Although there were different epidemics in our country, the two that had the most significant impact on later memory were cholera and yellow fever. These epidemics occurred, in different waves, in an almost simultaneous period of history in the 1860s and 1870s. Both cases were studied by historian Maximiliano Fiquepron in a beautiful book entitled Morir en las grandes pestes: Las epidemias de cólera y fiebre amarilla en la Buenos Aires del siglo XIX (To Die in the Great Plagues: Cholera and yellow fever epidemics in 19th century Buenos Aires.)In the case of cholera, it is possible to say that it left us with a political lesson: it was necessary to have a law of acephaly, to decide what to do in case of absence of the president and vice president. During that epidemic, President Bartolomé Mitre was leading the army in the Paraguayan war and the vice-president, Marcos Paz, was governing during his absence. However, Paz caught cholera and died on January 2, 1868. The big problem was that there was no law establishing who should succeed him. As Fiquepron analyzed, ministers wrote desperately to Mitre to get him to return, but in the 19th century, transportation and communication conditions made the process very slow (2). Therefore, for 15 days, in the middle of the epidemic, there was no one in charge of the executive branch. When the next president, Domingo Faustino Sarmiento, took office in 1868, one of the laws he passed was the Law of President Succession (Ley de Acefalía), so that in case of absence of the president and vice-president, the provisional president of the Senate would take over. Another possible learning experience that Sarmiento made was demonstrated when in 1871, during his administration, the yellow fever epidemic began in Buenos Aires. One of the president's first actions was to leave the city, to Mercedes, with the vice-president in order to avoid contagion.An action highly questioned in the public opinion of the time, but politically understandable in light of the previous epidemic.In the case of yellow fever, whose strongest and most remembered wave occurred in Buenos Aires in 1871, there was a story that survived in memory and that contrasts with what has been analyzed by historians such as Maximiliano Fiquepron (3). The traditional account of the epidemic held that the State was absent and emphasized the role of civilians and popular commissions in helping the sick and organizing the city in the face of the disease.However, for Fiquepron, the State learned during the epidemic how to deal with these public health problems. Thus, new institutions and reform bills were generated in areas such as health and public works.In closing, it is pertinent to point out that epidemics leave deep traces in society, economy, politics, social imaginaries, daily life and art.However, not all of them generate the same impact and, therefore, not all of them leave equally deep learnings. In this sense, in light of the past, we could ask ourselves if the COVID-19 epidemic will leave traces that will change the physiognomy of society or if it will be just another moment in the past that will go unremembered by later generations. References1. Snowden, Frank, Epidemics and Society: From the Black Death to the Present, Yale University Press, 2019. 2. Fiquepron, Maximiliano, Morir en las grandes pestes: Las epidemias de cólera y fiebre amarilla en la Buenos Aires del siglo XIX , Siglo Veintiuno, 2020.
Keywords: epidemic; history; COVID-19; quarantine